2019
DOI: 10.1111/weng.12404
|View full text |Cite
|
Sign up to set email alerts
|

Quotative like in the Englishes of the Outer and Expanding Circles

Abstract: The study aims at revising the major dichotomy between the Outer and Expanding Circles respectively. Taking the traditional sociolinguistic model of world Englishes as a starting point of discussion, I discuss the argument that classical macrosociolinguistic descriptions of linguistic varieties are helpful accounts that have also proven to be useful heuristic devices in the study of global variation as it is attested in English. Taking the linguistic variable ‘quotatives’ for illustration, I show that the patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(53 reference statements)
2
3
0
1
Order By: Relevance
“…The quote type was not selected as significant in a model that considers all of the predictors simultaneously, a finding previously reported in Davydova (2015) and Davydova and Buchstaller (2015). In line with the previous investigations of quotative marking by adult learners (Davydova, 2019a, 2019b, 2021), the learner grammar reported in Table 3 exhibits many of the properties reported for native‐speaker systems. I will take up this issue in the ensuing discussion of findings.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The quote type was not selected as significant in a model that considers all of the predictors simultaneously, a finding previously reported in Davydova (2015) and Davydova and Buchstaller (2015). In line with the previous investigations of quotative marking by adult learners (Davydova, 2019a, 2019b, 2021), the learner grammar reported in Table 3 exhibits many of the properties reported for native‐speaker systems. I will take up this issue in the ensuing discussion of findings.…”
Section: Resultssupporting
confidence: 85%
“…Drawing on data collected from a cohort of German learners, the study reported here has tested a set of social and sociopsychological variables in order to explore how these mediate acquisition of sociolinguistic competence in learners mastering English as a foreign language. While drawing on the domain of quotative marking as a diagnostic baseline, the study brings forth evidence demonstrating German learners’ largely wholesale acquisition of the target language patterns of variation, a finding consistent with previous research (Davydova, 2019a, 2019b, 2021, 2022; Davydova & Buchstaller, 2015). It also highlights the relevance of age, gender as well as learners’ linguistic identity to the process of mastering vernacular variation.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Kačru je formulisao jedan od najznačajnijih teorijskih modela, koji istraživači engleskog jezika u međunarodnoj upotrebi veoma često koriste kao polaznu tačku u svojim razmatranjima -model tri kruga (v. npr. Yamanaka 2006;Kang 2015;Davydova 2019). Kako Kačru navodi, sve zemlje u kojima žive govornici engleskog jezika mogu se podeliti u tri grupe -unutrašnji krug, spoljašnji krug i širi krug (Kachru 1992: 3).…”
Section: Svetski Varijeteti Engleskog -Sve (Engl World Englishes -We)unclassified